Novel inhaled andrographolide for treatment of lung cancer: in vitro assessment - Masarudin, Mas Jaffri; Jothi. N, Arul; Mohtar, Noratiqah; Parumasivam, Thaigarajan (Elsevier Ltd, 2024)
Andrographolide is a plant-based compound that showed promising activity against lung cancer. However, the compound's poor water solubility and low bioavailability limit its oral administration. Inhaled drug delivery of andrographolide is highly favourable as it delivers active ingredients directly into the affected lungs. In the current study, we compared in vitro aerosol performance, anti-cancer activity and storages stability of two (2) inhalable andrographolide formulations. Formulation 1 was prepared using precipitation and spray drying techniques, while Formulation 2 was prepared via direct spray drying technique. Drug morphology and physicochemical properties were confirmed using scanning electron microscopy (SEM) and X-ray diffraction (XRD) analysis. In vitro aerosol dispersion profile was evaluated using the next-generation impactor (NGI). Formulation 1 consisted of elongated crystals while Formulation 2 was made up of amorphous spherical particles. Both formulations had an inhalable fraction (<5 μm) of more than 40 %, making them suitable for pulmonary drug delivery. The formulations also showed an IC25 of less than 100 μg/mL against the human lung carcinoma cells (A549). Formulation 1 and 2 was stable in a vacuum condition at 30 °C for up to 6 and 3 months, respectively. Novel inhalable andrographolide dry powders were successfully produced with a good aerosol profile, potent anti-cancer activity and adequate storage stability, which deserve further in vivo investigations.